Successful supervision and leadership : ensuring high-performance outcomes using the pase model - Harris, Tracey (New York : Productivity Press, 2020)
Around the world, hundreds of thousands of supervisors and leaders provide coaching, supervision and leadership to staff every day of the year, yet the majority of supervisors have never attended formal training about how to be an effective supervisor and leader. The majority of supervisors do not refresh their skills, knowledge and capabilities to remain up to date or evaluate their supervisory practice regularly. Supervision is fundamental to ensure that employees meet the requirements of their role, feel supported and valued, and engage in ongoing growth and development. When supervision is effective, it reduces stress, fatigue and burnout. Supervision ensures that employees reflect on their work to maintain high performance and it supports well-being as a professional. This latest book is an essential guide for experienced supervisors and leaders. It is a comprehensive book demonstrating how to provide effective supervision and leadership in the modern workplace. It assists leaders to understand the industrial and ethical context in which supervision is provided, how to evaluate the effectiveness of supervision, and shows supervisors and leaders the specific capabilities that are necessary to be a quality leader and supervisor. This book is a must-read for any supervisor or leader who wants to provide effective supervision and leadership. Each chapter provides valuable information and the latest research on supervision with reflective questions to guide supervisors in their thinking and learning about supervision.
OCLC-licensed vendor bibliographic record.
Keywords: Supervision of employees; Leadership; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science